2011
DOI: 10.1007/s00213-011-2455-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cocaine-induced reinstatement by group II metabotropic glutamate receptors in the ventral tegmental area

Abstract: Our data support the idea that glutamate release in the VTA is critically involved in cocaine-induced reinstatement and indicate that loss of mGluR2/3-mediated regulation of glutamate release in the VTA may critically contribute to the risk of relapse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 63 publications
(84 reference statements)
0
15
0
Order By: Relevance
“…Thus, our mice experiments represent a first step toward the dissection between mGluR2 and mGluR3 functions in reward processing. Earlier rat experiments using the same behavioral models that we used with mGluR3 À / À mice reported that LY379268 may block motivation for cocaine in escalated rats (Hao et al, 2010) and decreased cocaine self-administration and cue-induced reinstatement in short-access cocaine-experienced rats (Baptista et al, 2004;Lu et al, 2012). Since LY379268 does not differentiate between mGluR2 and mGluR3, our mice experiments suggest a prominent role of mGluR2 in cocaine-seeking behavior.…”
Section: Discussionmentioning
confidence: 53%
“…Thus, our mice experiments represent a first step toward the dissection between mGluR2 and mGluR3 functions in reward processing. Earlier rat experiments using the same behavioral models that we used with mGluR3 À / À mice reported that LY379268 may block motivation for cocaine in escalated rats (Hao et al, 2010) and decreased cocaine self-administration and cue-induced reinstatement in short-access cocaine-experienced rats (Baptista et al, 2004;Lu et al, 2012). Since LY379268 does not differentiate between mGluR2 and mGluR3, our mice experiments suggest a prominent role of mGluR2 in cocaine-seeking behavior.…”
Section: Discussionmentioning
confidence: 53%
“…However, a more recent report demonstrated a reduction in nicotine self-administration by LY379268, but no effect on cocaine self-administration (Justinova et al, 2016). Although few studies have examined the circuitry by which mGlu 2/3 activation reduces drug self-administration, experiments evaluating cocaine and nicotine self-administration have implicated both VTA and NAc receptor populations as potential mediators of reduced drug intake (Liechti et al, 2007; Lu et al, 2012). …”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…Infusion of LY379268 into the rat VTA reduces context-induced reinstatement of heroin seeking (Bossert et al, 2004) and priming-induced resintatement of cocaine seeking (Lu et al, 2012). In addition, activation of group II mGlu receptors in the CeA prevents cue-induced reinstatement of cocaine seeking following prolonged extinction training (incubation of craving; Lu et al, 2007).…”
Section: Group II Metabotropic Glutamate Receptorsmentioning
confidence: 99%
“…Among drugs of abuse, the reinforcing/rewarding properties of cocaine (Sari et al, 2009, Li et al, 2010, Moussawi et al, 2011, Lu et al, 2012), heroin (Bossert et al, 2012) and ethanol (Obara et al, 2009, Cannady et al, 2011, Sari et al, 2011, Bahi et al, 2012) have been shown to interact with the glutamatergic system at various brain reward regions.…”
Section: Introductionmentioning
confidence: 99%